ClimeGreAq: A software-based DSS for the climate change adaptation of Greek aquaculture. (September 2021) - Stavrakidis-Zachou, Orestis; Sturm, Astrid; Lika, Konstadia; Wätzold, Frank; Papandroulakis, Nikos
Abstract: Climate change poses increasing challenges to aquaculture, resulting in the need to develop appropriate tools to assess these challenges and support decision-making. We present ClimeGreAq, a software-based Decision Support System (DSS) co-created with stakeholders to support the adaptation of Greek aquaculture to climate change. The DSS is based on an integrated modeling approach which links a biological and an economic model in order to simulate the effects of climate drivers on Greek aquaculture in a spatially heterogeneous manner. The tool may be used by stakeholders including farmers, producer organizations, regional administrations and national authorities to support decision-making on questions ranging from selecting appropriate farming locations, to designating zones for aquaculture activities, to developing national climate adaptation plans. Along with a description of the DSS design process, its structure, and the constituent models, key results are presented relating to stakeholder involvement, the user interface, and several application examples. Highlights: A DSS for Greek aquaculture was developed in collaboration with stakeholders. The DSS simulates and visualizes effects of climate change on fish and farm economics. The DSS may facilitate strategic decisions for aquaculture in the future.